Gaya Komunikasi Pengurus dan Hubungannya dengan Kepuasan Komunikasi Pekerja di Zoo Negara - Badrohisam, Othman (2011)
Communication is a dynamic process and it happens in all organizations. As a manager in an organization the skill of communication is crucial because the ability to communicate is a managerial necessity. Good managers are good communicators; poor managers are most often poor communicators. Therefore this quote summarizes the assumed importance of the relationship between communication and management. On this note too manager's communication style will affect the workers' communication satisfaction. Therefore the objective of this survey is to identify the correlation between the managers' communication style towards the workers' communication satisfaction using stratified random sampling, a set of questionnaire consisting of 48 items has been distributed 100 respondents from a population of 133 workers at the Zoo Negara. Seven dimensions managerial communication has been chosen for this survey and seven hypotheses have also been constructed to be tested in this study. Analysis factor had been supplemented to discover which of the 8 factors that been used influence the satisfaction in communication among Zoo Negara's staff. As a result, only 5 factors had been discovered to give an influence to the communication's satisfaction among them. From the 48 items that had been examined, only 30 items had found to lead on the satisfaction in communication among Zoo Negara's staff. Using Pearson Correlation r and the Mean Test, findings revealed that the entire four null hypotheses were rejected because there is a significant correlation between the managers' communication style towards the workers' communication satisfaction. It is hoped that this findings will give some insight to the administrators, programmed planners and trainers as to how effective managerial communication is, especially to the administrators at Zoo Negara in handling and interacting with their workers toward a better rapport between administrators and workers.